Konsep Memaafkan dalam Psikologi Positif - Ulin Nihayah; Salsabila Ade Putri; Rahmat Hidayat (Institut Agama Islam Negeri Kerinci, Indonesia, 2021)
Forgiveness is a very important positive force that exists within a person so as not to always be trapped in a negative emotional state which can proceed to release all negative emotions such as feelings of anger, feelings of hatred, hurt and even the desire to take revenge for others. how others treat us. Forgiveness is also included in a concept contained in the study of positive psychology which according to Martin Seligman that positive psychology does not only focus on a person's weakness or mental illness but also focuses on the positive strengths possessed by each person to regulate these negative emotions into a positive emotion. One way to develop yourself is by forgiving. Forgiveness has a very important role in a person's mental health, where when an individual is having feelings of anger, hurt, disappointment, and feelings of hatred towards others, this can increase the negative emotions that exist within the individual which can later cause stress. frustration, sadness and even the desire to take revenge against someone because they have harbored these negative emotions for too long which are eventually released with revenge. Forgiveness is very important because forgiving is a way to release all negative emotions that exist in a person and when successfully released it will have positive impacts that can be felt by the person, especially the positive impact on his mental health, which forgiveness will create feelings a person becomes more relieved, feels better, and the mood becomes calmer and more comfortable, therefore forgiveness is very important to do. The purpose of thr journal writing is, 1) to understand the concept of forgiveness within positive psychology, 2) understanding the relationship between forgivrness and mental health, 3) understanding the importance of forgiveness toward mental health.Descriptive qualitative writing method used in this study is to describe several important concepts that will be discussed so that they are clearer and easier to understand. The results of the study show that people who always forgive will make themselves calmer and make the quality of their lives better because basically forgiveness has a very clear urgency, especially in a person's mental health condition.